Costa Rican oral health: analysis of the situation in recent years - López Torres, Ana Cristina (2020)
Costa Rica has presented progress in oral health indicators in the last 10 years due to its National Health System structure. Health care services are divided into public, private and mixed services. The Costa Rican Social Security Fund is the entity that dominates the public sector and is the main one, divided into three tiered levels of care. This article seeks to expose the structure of the institutions that make up the surveillance and care of the most prevalent oral diseases in the Costa Rican population. In the same way, it presents the progress of these conditions through the last years. It is concluded that, despite the progress made, inter-institutional strengthening is necessary to face the challenges in the current oral health situation.